Impact of the Torsion on the Optoelectronic Properties of Poly(3-alkylthiophene): A Spectroscopic and Theoretical approaches - BOUZZINE, S.M.; BOUZAKRAOUI, S.; HAMIDI, M.; BOUACHRINE, M. (Asian Journal of Chemistry, 2010)
The aim of this work is to study the influence of the regioregularity of alkyl substituents on the poly(3-alkylthiophene) properties using UV-vis spectroscopy and theoretical analysis. It is found that the head-to-head sequences produce a steric hindrance and reduce the π-conjugation. Conformationals and optoelectroniques properties are greatly influenced by the type of the polymer's junctions.